1995
DOI: 10.1002/jhet.5570320342
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 5‐hydroxymethylfurfural and derivatives to furanaldehydes with 2,2,6,6‐tetramethylpiperidine oxide radical ‐ co‐oxidant pairs

Abstract: The oxidation of 5‐hydroxymethylfurfural (1) or 5‐hydroxymethylfurfurylideneacetophenone (4) with various 4‐substituted 2,2,6,6‐tetramethylpiperidine radicals (TEMPO) 3a‐d and supporting co‐oxidants gave corresponding aldehydes 2 or 5 in fair yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…Selective oxidation of the hydroxyl group of HMF, therefore, strongly required to form DFF. DFF synthesis had been examined using classical oxidants, including BaMnO 4 , pyridinium chlorochromate, NaOCl, and 2,2,6,6-tetramethylpiperydine-1-oxide (TEMPO), and also demonstrated by homogeneous metal bromide (Co/Mn/ Br) catalysts via autoxidation [191][192][193][194]. Furthermore, vanadium-based catalysts including V 2 O 5 [195], VOPO 4 Á 2H 2 O [196], and a V-containing polymeric catalyst [197] have been used previously.…”
Section: Synthesis Of Dialdehyde Via Selective Oxidations Of Functionmentioning
confidence: 99%
“…Selective oxidation of the hydroxyl group of HMF, therefore, strongly required to form DFF. DFF synthesis had been examined using classical oxidants, including BaMnO 4 , pyridinium chlorochromate, NaOCl, and 2,2,6,6-tetramethylpiperydine-1-oxide (TEMPO), and also demonstrated by homogeneous metal bromide (Co/Mn/ Br) catalysts via autoxidation [191][192][193][194]. Furthermore, vanadium-based catalysts including V 2 O 5 [195], VOPO 4 Á 2H 2 O [196], and a V-containing polymeric catalyst [197] have been used previously.…”
Section: Synthesis Of Dialdehyde Via Selective Oxidations Of Functionmentioning
confidence: 99%
“…Cottier et al 104 reported the oxidation of HMF with various 4-substituted 2,2,6,6-tetramethylpiperidine-1-oxide (TEMPO) free radicals and supporting co-oxidants. They tested a variety of co-oxidants such as calcium hypochlorite, sodium hypochlorite-potassium bromide, copper (I) chloride-oxygen pair, p-toluenesulfonic acid, iodine in alkaline conditions or the electrochemically generated Br radical.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] Nevertheless, the requirement of stoichiometric oxidants and the release of hazardous wastes are unavoidable for these methods. Therefore, selective oxidation of HMF to DFF with environment friendly molecular oxygen as oxidant satisfied the requirement of green chemistry.…”
Section: Introductionmentioning
confidence: 99%